(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Due to the increase in the frequency of fires due to the mass distribution of energy storage devices, following the introduction and operation of eco-friendly power generation facilities around the world, there is an urgent need to analyze the causes of such fires and to devise countermeasures against them. By analyzing the occurrence of ESS fires and reviewing the definition of ESS terminology, we intend to suggest some safety measures against ESS fires by understanding the related facilities and analyzing the causes. We would also like to propose new measures to prevent the spread of ESS fires. ESS fires occur most frequently during the discharge standby period after charging is completed in connected solar and wind power facilities. In addition, when we investigated the problems with the batteries, PCS manufacturing, ESS design, installation and construction, and the factors related to their usage and operation, we found such causes of fire as battery system defects, unsatisfactory protection systems against electrical shock, improper operations and environmental management, careless installations, and a lack of ESS integrated management systems. Therefore, a new approach is needed through the application of new technologies and safety measures including manufacturing standards, installation standards, operation and management standards, and firefighting standards for the purpose of ensuring the safety of these facilities and their operations, in order to prevent ESS fire accidents and the spread of fire.